1956
DOI: 10.1002/jsfa.2740071207
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of leaf protein concentrates. I.—Effect of addition of cholesterol and amino‐acids

Abstract: The value of leaf protein concentrates as supplements to cereal diets for chicks has been studied using the ‘gross protein value’ technique. Protein concentrates from different crops have been found to vary widely in nutritive value, but have in all cases been inferior to casein. Concentrates from lucerne contained a factor depressing chick growth, the effect of which was counteracted by adding cholesterol to the diets. This factor was not found in concentrates from Italian ryegrass or white clover. The additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Alfalfa contains tri-terpenoid saponins that are known to inhibit chick growth by limiting feed intake 23 and possibly…”
Section: Utilization Of Alfalfa Leaf Protein Concentrates For Livestockmentioning
confidence: 99%
“…Alfalfa contains tri-terpenoid saponins that are known to inhibit chick growth by limiting feed intake 23 and possibly…”
Section: Utilization Of Alfalfa Leaf Protein Concentrates For Livestockmentioning
confidence: 99%
“…The nutritional qualites of the plant juice and the protein‐rich concentrate for monogastrics have been evaluated in earlier studies focusing mainly on chickens, pigs or rats; however, the results obtained are not consistent. Some studies have demonstrated an improved growth of rats, as well as improved performance, weight gain and meat quality of pigs, when they are fed with plant juice or plant protein concentrate, whereas other studies have reported the opposite . An improper processing of plant material has been suggested to be one cause of the inconsistency in protein quality, but improvements in methods for green plant processing and protein extraction, combined with the increasing need for animal protein fuel new attempts to produce high‐quality protein alternatives to soy protein for animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated an improved growth of rats, as well as improved performance, weight gain and meat quality of pigs, when they are fed with plant juice or plant protein concentrate, whereas other studies have reported the opposite. [17][18][19][20][21][22][23][24][25][26] An improper processing of plant material has been suggested to be one cause of the inconsistency in protein quality, 10 but improvements in methods for green plant processing and protein extraction, combined with the increasing need for animal protein fuel new attempts to produce high-quality protein alternatives to soy protein for animal feed. White clover has high protein content and a balanced amino acid composition comparable to that of soy, making the plant an interesting candidate as a raw material for protein production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ford (1977), PEG increases methionine availability in the presence of tannins; Rambourg and Monties (1981) found no tannins but did detect flavonoidtype phenolics in a protein preparation from lucerne. It has been found (Cawlishaw et al 1956;Stojanovic 1979) that the addition of cholesterol improves the nutritive value of LPC from lucerne for rats and chicks. Larson and Halverson (1962) suggested that this improvement is a result of neutralisation of saponins present in lucerne juice.…”
Section: Discussionmentioning
confidence: 99%